Clinical Overrides With the YLS/CMI: Predictive Validity and Associated Factors - Parent, Geneviève (Criminal justice and behavior, 2023)
This study explores the use of clinical override with the Youth Level of Service/Case Management Inventory (YLS/CMI), including implications for predictive validity as well as the factors associated with this practice. The sample included 597 justice-involved youth from a metropolitan region in Québec, Canada. The clinical override was used in 32.5% of cases, usually to increase risk levels (30.3% of cases). As found in previous studies, clinical override did not increase the predictive validity of the YLS/CMI. Upward and downward clinical overrides were differently linked to the sociodemographic characteristics and criminal history of the youths in the sample. Criminal History, Peer Relations, Personality/Behavior, and Attitudes/Orientation risk/need domains were positively associated with upward override while Family Circumstances/Parenting, Personality/Behavior, and Attitudes/Orientation risk/need domains were negatively associated with downward override. These results are discussed in relation to the impact clinical override can have on the case management and interventions provided to justice-involved youth.